Consuming entertainment as Roamers: A study of generation Z’s television viewership in the digital era - Wibowo, Tangguh Okta; Syafuddin, Khairul; Elmada, Maria Advenita Gita (ProTVF, 2024)
Background: Before the digital era, television was spotlighted for people who enjoyed audio-visual shows. However, in the digital era, television viewers in Indonesia have decreased. The ease of access to infrastructure, the Internet, and mobile technology devices makes viewers, especially Generation Z (Gen-Z), prefer shows that can be enjoyed flexibly anytime and anywhere. Purpose: This paper discusses the trend of television viewers for Gen-Z amid the “onslaught” of streaming platforms. Methods: This study uses a survey method on Gen-Z, interpreted descriptively and qualitatively. Results: Based on the data obtained, this research illustrates that Gen-Z viewers can be said to be roamers or viewers who enjoy broadcast shows that move between streaming platforms. The study results show that the digital era has changed Gen-Z viewers’ behavior according to their technological devices and subscription streaming platforms. Conclusion: This research indirectly shows that the digital era and the presence of streaming platforms have made viewers increasingly fragmented, so television is not famous for Gen-Z to enjoy audio-visual shows, especially entertainment. Implications: The theoretical implication is that this roaming behavior may be a typical characteristic of Gen-Z. Future research could explore whether this behavior excludes Gen-Z or represents a broader trend among the emerging generation.